1995
DOI: 10.1073/pnas.92.21.9717
|View full text |Cite
|
Sign up to set email alerts
|

Neighboring base composition and transversion/transition bias in a comparison of rice and maize chloroplast noncoding regions.

Abstract: The correspondence between the transversion/transition ratio and the neighboring base composition in chloroplast DNA is examined. For 18 noncoding regions of the chloroplast genome, alignments between rice (Oryza sativa) and maize (Zea mays) were generated by two different methods. Difficulties of aligning noncoding DNA are discussed, and the alignments are analyzed in a manner that reduces alignment artifacts. Sequence divergence is <10%, so multiple substitutions at a site are assumed to be rare. Observed su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
78
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 16 publications
11
78
3
Order By: Relevance
“…However, the A 4 T transversions were the least frequent in humans (7.42%) and cattle (6.14%), while the C 4 G substitutions were the least frequent in mouse (6.37%) and Atlantic salmon (8%) (Hayes et al 2007). Interestingly, when two immediate adjacent sites flanking the SNPs were A 1 T rich (A 1 T content of 2, in particular), the frequency of transversional mutations significantly increased in animals, such as cattle (38.56%), human (38.70%), and mouse (36.50%), and in plants, such as Arabidopsis (53%) (Zhang and Zhao 2004) and the rice and maize chloroplast noncoding regions (57%) (Morton 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the A 4 T transversions were the least frequent in humans (7.42%) and cattle (6.14%), while the C 4 G substitutions were the least frequent in mouse (6.37%) and Atlantic salmon (8%) (Hayes et al 2007). Interestingly, when two immediate adjacent sites flanking the SNPs were A 1 T rich (A 1 T content of 2, in particular), the frequency of transversional mutations significantly increased in animals, such as cattle (38.56%), human (38.70%), and mouse (36.50%), and in plants, such as Arabidopsis (53%) (Zhang and Zhao 2004) and the rice and maize chloroplast noncoding regions (57%) (Morton 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely believed that the hypermutability effects of CpG dinucleotide sites contribute significantly to the increased rate of transitions in both plant and animal genomes as a result of deamination of methylated cytosines (Duncan and Miller 1980). However, the A 1 T content of the two immediate sites adjacent to the mutation sites is associated with an increased rate of transversion in the 1 nuclear genomes of human, mouse, and Arabidopsis (Zhang and Zhao 2004) as well as in the chloroplast genomes of rice and maize (Morton 1995). Interestingly, the two adjacent nucleotide sites that flank the mutations also show the largest biases compared to the genomewide and chromosome-specific average (Zhao and Boerwinkle 2002;Zhang and Zhao 2004).…”
mentioning
confidence: 97%
“…Context dependency of mutations has also been studied in grass chloroplast DNA (cpDNA; Morton 1995Morton , 2003. In this genome there is a significant correlation between the A 1 T content of the two sites flanking a mutation (the A/T context) and both the overall substitution rate and the transition:transversion (Ts:Tv) bias, due to a decreasing rate of transition substitutions as the A/T context increases (Morton 2003).…”
mentioning
confidence: 99%
“…A number of analyses of mutations have demonstrated that context, or the composition of nucleotides flanking a mutation, can have a significant influence on both mutation bias and overall mutation rate (Bulmer 1986;Morton 1995;Krawczak et al 1998;Zhao and Boerwinkle 2002;Morton 2003). Although context effects are not often considered in studies that apply mutation parameters (although see Arndt et al 2003;Siepel and Haussler 2003), there is evidence that understanding and incorporating such effects may be very important for interpreting genomic data (Morton 2003;Siepel and Haussler 2003) since they can result in variation in mutation dynamics across sites.…”
mentioning
confidence: 99%
“…However, in humans previous analyses of SNP variation and neighboringnucleotide effects have largely been limited to pseudogenes or a limited number of genes with known effects, many of which are disease-causing (e.g., Gojobori et al 1982;Li et al 1984;Cooper and Krawczak 1990;Krawczak et al 1998). In plants, effects of neighboring nucleotides have been extensively studied in chloroplasts (e.g., Morton 1995;Morton et al 1997).…”
mentioning
confidence: 99%